Intestinal Stem Cells: Common Signal Pathways, Human Disease Correlation, and Implications for Therapies. (26th December 2012) - Dalal, Jignesh; Radhi, Mohamed
Abstract : Enterocytes originating from gastrointestinal stem cells are basic building blocks of villi and crypts in human intestine. Little is known about intestinal stem cells (ISCs), their interaction with niche, and key pathways in their regulation. In this paper, we have reviewed the characteristics of ISC, its interaction with niche, and the understanding of key signaling pathways like Wnt. A better understanding of all of this will help to better utilize novel therapies like mesenchymal stromal cells (MSCs), R-spondin1, and sulindac in various disorders like colon cancer, graft-versus-host disease, intestinal polyposis, and radiation-related bowel injuries.